KEPEMIMPINAN ADAPTIF DALAM PENILAIAN KINERJA KEPALA MADRASAH UNTUK PENGUATAN MUTU PENDIDIKAN - Arfiani Yulianti Fiyul (Perkumpulan Peneliti dan Pegiat Literasi, 2026)
This study examines how adaptive leadership shapes the implementation of the Principal Performance Appraisal in public madrasahs as a mechanism for improving educational quality. It addresses the gap between the formal policy design of the appraisal system and its practical enactment at the school level. A qualitative approach with a descriptive case study design was employed. Data were collected through semi-structured interviews, field observations, and document analysis involving selected principals of public madrasahs in Sukabumi Regency. The data were analyzed thematically using the Miles and Huberman interactive model, supported by source triangulation and data verification. The findings show that adaptive leadership enables principals to translate policy demands into context-sensitive school practices, manage resistance to change, and foster collaborative quality improvement. Principals who exercised adaptive leadership promoted teacher participation, strengthened internal coordination, and developed locally grounded strategies for quality assurance. These findings indicate that adaptive leadership is crucial for bridging national policy expectations and institutional realities in madrasahs. This study contributes to the literature by offering a contextual model of Islamic educational leadership that is practical, responsive, and relevant to quality improvement in public madrasahs.